KONSENTRASI DAN INTERVAL APLIKASI PUPUK ORGANIK CAIR Amazing Bio-Growth TERHADAP KOMPONEN HASIL TANAMAN KACANG HIJAU (Phaseolus radiate L.) VARIETAS LOKAL SABU - Maria Klara Salli; Masria Masria (Partner, 2021)
The purpose of this study was to obtain the best concentration and interval of application of POC ABG to increase the yield of local varieties of mung bean Sabu.RBD with two factors was used in this study namely, factor 1(concentration): 2, 4, 6, and 8 ml LOF/liter of water; factor 2 (interval): 7 and 14 days once. Data were analyzed using ANOVA and further test using DMRT 5%.The results showed that there was no effect of POC ABG treatment on the number of seeds/pods and the weight of 100 seeds. POC ABG concentrations of 2 and 4 ml/liter of water and application intervals of 7 days gave the highest seed yields per plot (240.73 grams and 238.84 grams) and 240.66 grams. The interaction of treatment 4 ml/liter of water and application interval of 7 days gave the number of pods planted (15.22) and the highest seed yield (9.63 grams). Key Words:  Concentration, interval, ABG, mung beans local var Sabu